Impact of bariatric surgery on cardiovascular and renal complications of diabetes: a focus on clinical outcomes and putative mechanisms. Issue 5 (3rd September 2018) - Martin, William P.; Docherty, Neil G.; Le Roux, Carel W.
ABSTRACT: Introduction : Cardiovascular and renal disease accounts for a substantial proportion of the morbidity and mortality associated with obesity and type 2 diabetes mellitus (T2DM). Bariatric surgery is associated with improved long-term cardiovascular and renal outcomes. Areas covered : All major case-control, cohort, and randomized controlled trial studies of bariatric surgery in adults with T2DM were screened and data on prespecified cardiovascular and renal outcomes collated. Bariatric surgery reduces all-cause mortality and risk of cardiovascular disease, albuminuria and progressive chronic kidney disease. Patients with poorer glycemic control and established microvascular disease preoperatively may stand to benefit the most from the surgical approach. Reduced sympathetic drive, remission of glomerular hypertension, enhanced natriuresis, gut microbiota shifts, reduced systemic and renal inflammation, improved lipoprotein profiles, and reductions in chronic cardiac remodeling may all be implicated. Expert commentary : Ongoing RCTs of bariatric surgery selectively recruiting patients with class 1 obesity and established microvascular complications of diabetes will help to better characterize which subgroups of patients benefit most from this effective therapy.